The cost optimal control system based on the Kermack–Mckendrick worm propagation model. Issue 2 (June 2016) - Tong, Xiao-Jun; Zhang, Miao; Wang, Zhu
Although the network worm propagation models are able to predict trends in the spread of the worm, these papers did not consider the economic losses caused by the worm propagation. This paper uses the Hamiltonian approach of the optimal control theory and proposes the cost optical control system based on the Kermack–Mckendrick worm propagation model. In the cost optical control system, we control and process the infectious hosts. In this paper, we present an optimization model that takes into account infection cost and treatment cost. The simulation on the cost optical control system is carried out, and then the results of the analysis are given. In conclusion, the cost optical control system of the Kermack–Mckendrick model can provide the optical control of the worm propagating and effectively reduce the worm propagation with minimum cost.